Combined radiation and chemotherapy for squamous cell carcinoma of the anal canal: results and prognostic variables in a multiinstitutional series of 173 patients - Grabenbauer, Gerhard G. (Radiology and oncology (Ljubljana), 1997)
Purpose: This retrospective multicenter study was aimed to asses the effect ofcombined modality therapy in patients with squamous cell carcinoma of the anal canal, stage T1-4 NO-3 MO. Patients and methods: Between 1985 and 1994, 173 patients underwent treatment by combined radiation and chemotherapy. A median total dose of 50 Gy was delivered to the primary, perirectal, presacraland inguinal nodes, followed by a local boost in selected cases. 5-Fluorouracil was scheduled as a continuous infusion of 1000 mg/m2/24 h on days 1-5 and 29-33, and mitomycin C as bolus of 10 mg/m2 on days 1 and 29. Results: Cancer related survival (OS), NED-survival and local control rates at5 years were 71+-5%, 59+-4% and 67+-4%, respictively. Anorectal function waspreserved in 91% of the patients in whom the primary was controlled. Only 9.6% experienced severe late toxicity requiring surgery. In univariate analysis, T category (T1/2 vs. T3/4) was predictive for OS (83+-4% vs. 53+-9%,p=0.01), NED-surival (75+-4% vs. 36+-7%, p<0.0001) and local control (81+-4% vs. 46+-7%, p<0.0001). N category (NO vs. N1-3) influenced NED-servival (66+-5% vs. 33+-12%, p=0.004) and local control (76+-4% vs. 37+-13%, p=0.003). Treatment technique (<2 fields vs. 2 fields) was found to be of prognostic value for NED-surival (70+-6%, sv. 50+-6%, p=0.016) and localcontrol (77+-6% vs.58+-6%, p=0.018). Only in T3/4 cases the total RT-dose(<45 Gy vs. 45 Gy) had an impact on NED-survival (42+-7% vs. 23+-13%, p=0.01) and local control (52+-8% vs. 45+-15%, p=0.03). In multivariate analysis, the T category (UICC 1922) remained the only significant variable with impact on survival (p=0.04), NED-survival (p<0.001) and local control (p=0.003). Conclusion: Treatment with a combination of radiotherapy and chemotherapy is safe and effective for patients with anal canal carcinoma. Theimprovement of results in advanced stages is warranted.
Keywords: Carcinoma, squamous cell; Drug therapy; Fluorouracil; Mitomycin c; Multicenter studies; Neoplasm staging; Radiotherapy; Rectal neoplasms; Survival analysis; Treatment outcome